The R6 lines of transgenic mice: A model for screening new therapies for Huntington's disease - Gil, Joana M. (2009)
http://www.sciencedirect.com/science/article/B6SYS-4V59VTB-1/2/2a1ab641b7c1e5d4b9ca6f8c2134bdc0